ETR 300 : Chicken Run industry Sdn. Bhd. / Bismayazar Yusoff ...[et al.] - Yusoff, Bismayazar; Sy. Wafa, Sh. Zahrin; Abdullah, Noor Asyikin; Isahak, Siti Sarah (2003)
Chicken Run industry Sdn. Bhd. is an organization which produces chicken based food product. Our business is concentrated on the process from raw material to semi- finished goods and finally finished goods like satay, roasted chicken and others. We choose this business according to a high demand in food industries. As we read in news paper, Malaysia has been the biggest supplier of food to the world, so we want to become one of the supplier to the customers. Another that, our business is unique compare to same business similar like us. lt is because we process the chicken from raw material to semi- finished and lastly to finished goods and we think we can go far to diversify our product to all states in Malaysia. Our organization has agreed to choose Bandar Perda, as our location to start our business. We choose the place because of the strategic area which is near to our supplier. Another that it also have good infrastructure and situated at main road, so we can easily promote our product to our customers. The place also strategic because there are many shopping complex at that area, the demand for food increase highly, so we take this opportunities to open our business' here.